Monte Carlo Simulations of Impact Ionization Feedback in MOSFET Structures. Issue 1 (1998) - Bude, Jeff D.
Abstract : Although impact ionization feedback is recognized as an important current multiplication mechanism, its importance as a carrier heating mechanism has been largely overlooked. This work emphasizes the inclusion of impact ionization feedback in Monte Carlo device simulations, and its implications for carrier heating in sub-micron CMOS and EEPROM technologies.